Operationalizing inclusive innovation: Lessons from innovation platforms in livestock value chains in India and Mozambique - Swaans, Cornelis P.M.; Boogaard, Birgit K.; Bendapudi, R.; Taye, H.; Hendrickx, Saskia C.J.; Klerkx, Laurens (Informa UK Limited, 2014)
Various authors have identified the potential relevance of innovation system approaches for inclusive innovation, that is, the means by which new goods and services are developed for and by the poor. However, it is still a question how best to operationalize this. Innovation platforms (IPs) represent an example of putting an inclusive innovation system approach into practice by bringing different types of stakeholders together to address issues of mutual concern and interest with a specific focus on the marginalized poor. This paper explores the formation and functioning of IPs with the aim of providing lessons on the conditions and factors that play a role in making them effective. The study shows the importance of social organization, representation, and incentives to ensure a ‘true’ participatory innovation process, which is based on demand and embedded in the context. Critical to this is a flexible planning process stimulating incremental change through so-called innovation bundles (i.e. combinations of technological, organizational, and institutional innovations) and reflexive learning (systematically challenging constraining factors). Furthermore, local institutions embedded in norms and values are crucial to understand people's decisions. Due to weak linkages between value chain actors, innovation brokers have a vital role in facilitating the innovation process. Overall, IPs are a promising model for inclusive innovation, but they require a careful assessment of and adjustment to the institutional context.